Regresión y correlación de caracteres fenotípicos de cabras adaptadas en la parroquia Sabiango, cantón Macará, provincia de Loja, EC. - Armijos Castillo, Katherine Mariuxi (2017)
Aiming to study the correlation and regression of phenotypic characters in Creole goats, the relationship between live weight and some morphometric variables in adapted goats from the Sabiango parish was analyzed. The following measurements were taken: body length, length of the cane and thoracic perimeter for which 50 goats between 3 and 36 months of age, males and females, physiological state were used. Males and females, pregnant and no pregnant were including in this work. The following parameters were measuring: body length, length of the heel reed and heart girth. A correlation analysis was performed using the SAS PROC CORR procedure (Sas University Edition 2016). The PROC REG procedure was used to construct the regression model. Slopes with a P<0.05 were considered as significant. The use of the PROC MIXED procedure determined a non-significant effect of gender, physiological status and age on the relation between heart girth and body weight. The r2 , AIC and BIC criterions were used to select the best model. The best body weight estimator was the heart girth, the final equation obtained was: Live weight (kg) = - 49.3 (± 4.01) + 1.06 (± 0.0496) heart girth, with r2 = 0.904 and a P-value of slope <0.001. Finally, the “cinta caprinometrica” was created.